PENGARUH PEMANFAATAN WEBSITE PEMERINTAH KOTA BATAM TERHADAP KEPUASAN MASYARAKAT KOTA BATAM (SUATU SURVEI PADA KEC. SAGULUNG BATU AJI) - Mesri Silalahi (Universitas Putera Batam, 2013)
Problems faced before the portal Pemko Batam is in the slow to respond to any public complaints and the people themselves do not have containers for their aspirations, this suggests that the rate of utilization of the website Pemko Batam low public perception, the perceived level of satisfaction was less, the effect of the use of Batam City Government website for public satisfaction is low. The aim of this study was to determine how the level of utilization of Batam City Government website, to determine the effect of the use of Batam City Government website for public satisfaction peningkatkatan Batam city. The research method used was Deskriptik and verification which the descriptive method is used to analyze the frequency and distribution of the average perception of respondents and also verification to see the relationships and influences between variables, which influence the utilization WebSite indenpenden variable (X1) of the Community Satisfaction dependent variable (Y), with the resident population aged 16 years and over for 93 588 people. The findings of this study is the website Pemko Batam considered beneficial by the public, the website significantly affect the satisfaction of the people of Batam.